Comparison of two purified toxic fractions from Mesobuthus eupeus scorpion venom - Shirmardi,SP (2010)
Iranian scorpions belong mainly to the Buthidae and Scorpionidae families, distributed into 16 genera and 25 species. In Iran, similar to other parts of the world, there are a few known species of scorpions responsible for severe envenoming; amongst which Mesobuthus eupeus is the most common. Its venom contains several toxin fractions that may affect the ion channel. In the present study purification, labeling and biological evaluation of M. eupeus venom are described. For separation, soluble venom was loaded on a chromatography column packed with Sephadex G-50 gel. Subsequently, the fractions were collected according to UV absorption at a wavelength of 280 nm. Toxic fraction (F3) was loaded on an anionic ion exchanger resin and then on a cationic resin. Finally, toxic subfractions F3.1.6 and F3.1.9 were labeled with 99mTc and injected into normal mice to distinguish excretion pathway. The venom toxic fraction was successfully obtained in its purified form. Radiolabeling of toxic fractions was performed at high specific activity with radiochemical purity of more than 97 and 95% respectively for F3.1.6 and F3.1.9. Biodistribution studies in normal mice with two toxic fractions usually show rapid clearance of the compounds from blood and tissue except for kidneys. Since tissue distribution studies are very important for clinical purpose, the present findings suggest that 99mTc labeling of venom is a useful tool for in vivo studies and comprises an excellent approach to monitoring the process of biodistribution and kinetics of toxins.